‘Underestimation of fall risks by older adults: The need for professional evaluation to identify home hazards’ - E．Y Ishigaki; A．S Passos; L．E．G Leme (Archives of Gerontology and Geriatrics Plus)
Falls are a significant public health issue among older adults, often resulting in serious injuries and decreased quality of life. Approximately 30–50 % of falls are related to environmental factors, with 60 % occurring within the home. Objective: This study aims to analyze the extent to which Brazilian older adults accurately perceive fall risks in their home environment, emphasizing the potential gap between self-perception and actual hazards. Methods: 90 older adults were assessed through home visits using the Home Safety Self-Assessment Tool (HSSAT), an American instrument adapted for the Brazilian context. The HSSAT, a 67-item self-assessment tool covering nine household areas, was administered by trained researchers. Data were collected through both self-assessment by the older adults and assessments by healthcare professionals to analyze perception discrepancies. A test-retest analysis was also conducted with 30 participants. Results: Results showed that older adults identified an average of 5.1 risk factors, whereas healthcare professionals identified 12.6 on average, indicating low to moderate agreement between the two groups. The highest risk areas were the bathroom (25.6 %) and kitchen (20.2 %) in the self-assessment, while professionals found additional risks, especially in the bedroom (15.5 %) and kitchen (13.4 %). In the test-retest analysis, only nine items showed good agreement. Still, the second assessment revealed higher scores, suggesting improved risk perception due to a potential educational effect of the initial evaluation. Conclusion: These findings reveal that older adults significantly underestimate fall risks, amplifying the critical need for healthcare professionals to assess environmental hazards accurately.